Illumination Reduction for Low Contrast Color Image Enhancement with Homomorphic Filtering Technique - Vishwakarma, A. K.; Mishra, A.; Gaurav, K.; Katariya, A. (2012 International Conference on Communication Systems and Netework Technologies (CSNT), 2012)
Image clarity is very easily affected by lighting, weather, or equipment that has been used to capture the image. These conditions lead to image may suffer from loss of information. Quality of the image is highly affected by improper lighting condition or illumination. Therefore removal of such illumination and increase of Image quality is necessary for human perception. In this paper, we propose a novel approach for Illumination correction of such Images. The proposed method uses Homomorphic filtering technique to reduce illumination and compare the results with contrast limited adaptive histogram equalization (CLAHE) technique. Experimental results on test images corrupted by illumination pattern shows that results obtained are visually effective compared with the existing CLAHE method.